Management accounting ; module-I - Inamdar, Satish (Symbiosis Centre for Distance Learning, 2010)
Management accounting ; module-I / Inamdar, Satish. -- Pune: Symbiosis Centre for Distance Learning, 2010 658.1511 In35 No. of Copies : 1